2022
DOI: 10.1002/chem.202104431
|View full text |Cite
|
Sign up to set email alerts
|

Spin States, Bonding and Magnetism in Mixed‐Valence Iron(0)‐Iron(II) Complexes**

Abstract: We report the synthesis of two complexes featuring unsupported Fe-Fe bonds, L x Fe-Fp (L a = 3-methyl-2,4-bis(2,6-dimethylphenylimido)pentyl, L b = 1,3-bis (2,4,6trimethylphenylimido)propyl; Fp = Fe(CO)2Cp). Mössbauer spectroscopy, SQUID magnetometry and computational analysis indicate that the most accurate electronic structure description is LFe II -Fe 0 (CO)2Cp, in which the Fe(CO)2Cp is low spin iron(0) and acts as a Lewis base toward the high spin iron(II) of the LFe fragment which is a Lewis acid. In bot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The geometric parameters in 3 and 4 are typical of high-spin ( S = 2) Fe(II) complexes. The intramolecular Fe–Fe distances ( 3 : 3.5729(5) Å, 4 : 3.1293(7) and 3.1268(7) Å) are considerably longer than the sum of the covalent radii (2.50 Å), placing them outside the range of Fe–Fe bonds. , This is consistent with the effective magnetic moments of these complexes determined by the Evans method at room temperature, , which are μ eff = 6.7 μ B for 3 and μ eff = 6.8 μ B for 4 . These values are close to the spin-only value expected for two uncoupled (paramagnetic) high-spin iron(II) ions of μ eff = 2 × 4.90 = 6.93 . ,,, …”
Section: Results and Discussionsupporting
confidence: 74%
“…The geometric parameters in 3 and 4 are typical of high-spin ( S = 2) Fe(II) complexes. The intramolecular Fe–Fe distances ( 3 : 3.5729(5) Å, 4 : 3.1293(7) and 3.1268(7) Å) are considerably longer than the sum of the covalent radii (2.50 Å), placing them outside the range of Fe–Fe bonds. , This is consistent with the effective magnetic moments of these complexes determined by the Evans method at room temperature, , which are μ eff = 6.7 μ B for 3 and μ eff = 6.8 μ B for 4 . These values are close to the spin-only value expected for two uncoupled (paramagnetic) high-spin iron(II) ions of μ eff = 2 × 4.90 = 6.93 . ,,, …”
Section: Results and Discussionsupporting
confidence: 74%
“…Previous studies of (β-dialdiminato)iron complexes demonstrated their application in the formation of a bimetallic compound containing an unsupported Fe–Fe bond as well as the activation of white phosphorus (P 4 ). In the latter case, reaction of the iron­(I) species H LFe­(PhMe) with P 4 leads to a dinuclear compound in which the two iron centers are bridged by diphosphorus ligands . Further evaluation found that a related but distinct bimetallic complex forms with the methyl-substituted system …”
mentioning
confidence: 99%